Doing political science and international relations theories in action - Savigney, Heather; Marsden, Lee (Political Analysis, 2011)
This book provides a new type of introduction to politics and international relations that examines how, why, and what we study. Systematic and accessible in its approach, it introduces the analytical toolkits needed to study politics and international relations. The book takes a fully integrated approach to domestic and global politics, incorporating real-world case studies throughout.